2009
DOI: 10.1007/s00442-009-1330-0
|View full text |Cite
|
Sign up to set email alerts
|

Host species and habitat affect nodulation by specific Frankia genotypes in two species of Alnus in interior Alaska

Abstract: Alders (Alnus spp.) are important components of northern ecosystems due to their ability to fix nitrogen (N) in symbiosis with Frankia bacteria. Availability of optimal Frankia may be a contributing factor in limiting the performance and ecological effects of Alnus, but the factors underlying distribution of Alnus-infective Frankia are not well understood. This study examined the genetic structure (nifD-K spacer RFLP haplotypes) of Frankia assemblages symbiotic with two species of Alnus (A. tenuifolia and A. v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(67 citation statements)
references
References 70 publications
4
63
0
Order By: Relevance
“…The nonrandom distribution of genotypes between hosts is consistent with the results of previous studies covering a variety of host taxa and geographic locations (Van Dijk et al 1988;Rouvier et al 1996;Clawson et al 1999;Navarro et al 1999;Huguet et al 2001) as well as for Frankia assemblages captured on different actinorhizal species exposed to the same soil inoculum (Mirza et al 2009). In combination with host-associated Frankia distribution patterns at Alnus sites in Alaska (Anderson et al 2009) and Ceanothus sites in California (Oakley et al 2004), these results implicate host species identity as a key influence on the structure of Frankia assemblages in western North America.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The nonrandom distribution of genotypes between hosts is consistent with the results of previous studies covering a variety of host taxa and geographic locations (Van Dijk et al 1988;Rouvier et al 1996;Clawson et al 1999;Navarro et al 1999;Huguet et al 2001) as well as for Frankia assemblages captured on different actinorhizal species exposed to the same soil inoculum (Mirza et al 2009). In combination with host-associated Frankia distribution patterns at Alnus sites in Alaska (Anderson et al 2009) and Ceanothus sites in California (Oakley et al 2004), these results implicate host species identity as a key influence on the structure of Frankia assemblages in western North America.…”
Section: Discussionmentioning
confidence: 85%
“…Second, a number of prior studies examining host species effects in combination with other factors have found significant interactions. For example, many field-based studies have documented coincident effects of host species identity and Huguet et al 2001Huguet et al , 2004Oakley et al 2004;Anderson et al 2009). Other studies have found geography alone rather than host species identity was the best predictor of Frankia assemblage structure (Jeong and Myrold 1999;Ritchie and Myrold 1999).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While a considerable amount of information is available on nodule-forming populations, and the interaction of frankiae with host plant species [5,9], information on frankiae in soil, its second ecological niche, is relatively scarce [8]. Most of the information on soil Frankia populations focuses on their potential to form root nodules [19,35,36,39], diversity as a function of host plant species [1,2,23,35] and the effects of environmental characteristics on nodule-forming capacity [16,31,37,40]. Environmental characteristics such as soil organic matter and matric potential, for example, have been shown to affect the development of specific Frankia populations [17,18,20,21], with organic matter such as leaf litter supporting growth of one specific population, i.e., subgroup II of the Alnus host infection group represented by strain Ag45/Mut15 only [17].…”
mentioning
confidence: 99%
“…Symbiotic Frankia assemblages can differ widely between sympatric Alnus spp. and between successional habitats occupied by a given host species (Anderson et al 2009). Phylogenetic Tables 1 and 2 Trees specificity is a significant factor in the Alnus tenuifoliaFrankia interaction, and significant habitat-based differentiation may exist among A. tenuifolia-infective genotypes .…”
Section: Nodule Biomass In Alnus Standsmentioning
confidence: 99%